Analisis Laporan Keuangan PT. Mandom Indonesia Tbk menggunakan Metode Vertikal - Sony Widia Sari; Herdiyanti Ulan Andani; Fitra Aditia; Annisa Zulfa Majid; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Qualitative descriptive research is the kind of study that this is. The purpose of this study is to evaluate PT. Mandom Indonesia, Tbk's financial performance using a vertical analysis. The financial statements of PT. Mandom Indonesia Tbk for 20 years, with a 7-year sample, comprise the population in this study. outcomes of PT's balance sheet report's vertical analysis. Mandom Indonesia, Tbk has been at its best between 2015 and 2021. The total assets post, which is higher than the total liabilities post, illustrates this.